TAGUCHI EXPERIMENTAL DESIGN FOR ROASTING PARAMETER TO IMPROVE COFFEE POWDER QUALITY - Putro, Wisnu Wijayanto; Oktavianty, Oke; Novareza, Oyong; Swara, Suluh Elman; Rachmansyah, Ihram (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2024)
Quality improvement is important to reach customer satisfaction and gain the competitive advantage. This research was using the Taguchi experiment design to obtain a combination of roasting parameters, which could in turn improve the quality of coffee powder. During the roasting process, the acids that were naturally contained in coffee beans were transformed into acetic acid, malic acid, citric acid, and phosphoric acid, which in turn contributed to the coffee’s actual taste. Several key factors contributed to the taste of coffee powders, namely roasting temperature, roasting time, the weight per roasting, and cooling time. The significance factor to improve quality of Robusta coffee powder namely roasting temperature on 185 °C, roasting time in 20 minutes, weight per roasting is 7.5 kilograms and cooling time is 10 minutes. The organoleptic tests of the resulting coffee powders showed an average of 4.93 with regards to consumer rating. The experiment result revealed the optimal setting level that should be applied in the production process of coffee powders for gaining better quality and thus more favourable to consumers.